2018
DOI: 10.1111/gwat.12665
|View full text |Cite
|
Sign up to set email alerts
|

Quartz‐Helium Method to Estimate Fluid Flow in Thick Aquitards, Gunnedah Basin, Australia

Abstract: The hydraulic integrity of aquitards is generally assumed and relies on a few core-scale permeability measurements, drill-stem tests, or textbook values. This approach is because hydraulic data across the full aquitard thickness is generally lacking. Proper assessment of aquitard integrity should be studied at the formation (spanning its entire thickness at a single point) or regional (formation properties at multiple locations throughout the basin) scale. One formation-scale approach uses environmental tracer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The Gunnedah basin is unconformably located on the Permian or older basement and partially unconformably covered by sedimentary and volcanic rocks of the Jurassic and Cretaceous Surat Basin sequence [36]. The large-scale magmatic intrusion occurred in Late Triassic to Early Jurassic [37,38]. Figure 1 shows the geological map of the basin and the position of the target well used for numerical simulation.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The Gunnedah basin is unconformably located on the Permian or older basement and partially unconformably covered by sedimentary and volcanic rocks of the Jurassic and Cretaceous Surat Basin sequence [36]. The large-scale magmatic intrusion occurred in Late Triassic to Early Jurassic [37,38]. Figure 1 shows the geological map of the basin and the position of the target well used for numerical simulation.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Noble gases enclosed in rock minerals provide important insights about different evolutionary stages of minerals or rock formations and of geological processes, such as pressure-temperature conditions during ore/rock formation, the nature, provenance, and evolutionary history as well as ages of geofluids [25]. 40 Ar- 39 Ar chronology acts widely as a main application field (e.g., [26,27]). The main noble gas isotope ratios used for the identification of fluid inclusion origins in rock material representative of different geoscientific study areas (e.g., "crustal rock studies," "mantle rock studies," "ore rock studies," extraterrestrial rock studies," or "deepwater studies") are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, He isotope systematics are relatively well understood and have been described in many studies [28][29][30]. The combination of noble gas analysis and halogens of irradiated samples has been successful in studying 40 Ar/ 39 Ar age systematics [31]. Analysis of halogens (Cl, Br, I) in fluid inclusions can be also accomplished by measuring irradiationproduced stable noble gas isotopes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations